Pattern of childhood injury in a tertiary centre - Rotimi O Aderibigbe; Tolulope O Ogunrewo (Wolters Kluwer Medknow Publications, 2022)
Introduction: Childhood injury and death have been projected to be a disease of public health significance, however, the trend in many developing countries of which Nigeria is one is still unknown. We, therefore, examine the pattern of childhood traumatic injury in our institution. Materials and Methods: The information of patients aged 16 years and below who presented with trauma was extracted from the trauma registry of the emergency units of University College Hospital, Ibadan, from 2015 to 2020. Data were analysed using the SPSS version 20. Results: A total of 3146 children were managed for trauma in the accident and emergency departments of the hospital. Most of them were males (61.2%) and within the under-five age group (36.4%). The majority of the injuries were secondary to fall (41.8%). Male child was more likely to be involved in any mechanism of injury and children between 11 and 16 years were commonly involved in machine hand injury (80%). Following intervention in the accident and emergency department, 44.1% were discharged in the emergency units, 21.5% required admission into the specialist ward, 6.0% died, 5.0% discharged against medical advice and 2.6% were referred. Conclusion: The burden of childhood injury is becoming significant thus demands more attention.